The Importance of Object-based Seed Sampling for Superpixel Segmentation - Belém, Felipe de Castro; Melo, Leonardo; Guimaraes, Silvio; Falcao, Alexandre Xavier (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
Superpixel segmentation can be defined as an image partition into connected regions, such that image objects may be represented by the union of their superpixels. In this context, multiple iterations of superpixel segmentation from improved seed sets is a strategy exploited by several algorithms. The Iterative Spanning Forest (ISF) framework divides this strategy into three independent components: a seed sampling method, a superpixel delineation algorithm based on strength of connectedness between seeds and pixels, and a seed recomputation procedure. A recent work shows that object information can be added to each component of ISF such that the user can control the number of seeds inside the objects and so improve superpixel segmentation. However, no study has been conducted to evaluate the impact of object information in each component. In this work, we fulfill this gap with respect to the seed sampling component of ISF. We also propose a novel seed sampling approach, named Object Saliency Map sampling by Ordered Extraction (OSMOX), and demonstrate the results for supervised and unsupervised object information. The experiments show considerable improvements in under-segmentation error, specially with a low number of superpixels.